Is total aortic arch replacement with the frozen elephant trunk procedure reasonable in elderly patients?. (14th February 2021) - Beckmann, Erik; Martens, Andreas; Kaufeld, Tim; Natanov, Ruslan; Krueger, Heike; Haverich, Axel; Shrestha, Malakh
Abstract: OBJECTIVES: Total aortic arch replacement is an invasive procedure with significant risks for complications. These risks are even higher in older, multimorbid patients. The current trends in demographic changes in western countries with an ageing population will aggravate this issue. In this study, we present our experience with total aortic arch replacement using the frozen elephant trunk (FET) technique in septuagenarians. We compared the results of septuagenarians with those of younger patients and analysed if there was an improvement in outcome over time. METHODS: Between August 2001 and March 2020, 225 patients underwent non-urgent FET procedure at our institution. There were 75 patients aged ≥70 years (mean age 74 ± 4) who were assigned to group A, and 150 patients aged <70 years (mean age of 57 ± 11) who were assigned to group B. In groups A and B, the indications for surgery were chronic dissection (21% vs 53%), aortic aneurysm (78% vs 45%) and penetrating atherosclerotic ulcer (1% vs 2%). RESULTS: The rate for temporary dialysis was significantly higher in group A than in group B (29% vs 13%, P = 0.003), although the majority recovered kidney function. Rates for re-exploration for bleeding and stroke were comparable in both groups. In-hospital mortality was significantly higher in group A than in group B (24% vs 13%, P = 0.037). Logistic regression analysis showed that age >70 years was an independent statistically significant risk factor for in-hospital mortality (odds ratio = 2.513, 95% confidence interval = 1.197–5.278, P -value = 0.015). Follow-up was complete for 100% of patients and comprised a total of 1073 patient-years with a mean follow-up time of 4.8 ± 4.5 years. The 1- and 5-year survival rates were 68% and 49% in group A, and 85% and 71% in group B, respectively (log rank, P < 0.001). Survival did not significantly improve over time. Discussion: Total aortic arch replacement using the FET technique has a significantly higher risk for perioperative morbidity and mortality in septuagenarians than in younger patients. Long-term survival is significantly impaired in older patients. We recommend thorough patient selection of those who require total aortic arch replacement, and optimization of perioperative management to improve outcomes.